C. B interrupt duty reduction based controlling TRV and symmetrical breaking current. Issue 1 (31st December 2023) - Shalash, Nadheer A.; Lafta, Yasar N.; Lafta, Mafaza N.
Abstract: Evaluating the rated MVA sizes of the Circuit Breaker (CB) requires calculating reactance parameters from fault analysis and synchronizing these parameters with the reference re- striking voltage. In this paper two ways are used in controlling X/R ratio of the system to reduce CB size in order to save cost on system configuration. PSS/E program was introduced to facilitate and illustrate the solution. X/R ratio and subtransient reactance were calculated to provide an approach to assess the current and duty interruption of generator buses with contributions from all other buses. The effect of reduction factors and NACD for the symmetrical component of the short circuit current is also applied in our proposed method. The obtained results proved that applying the reduction factor technique in New England system reduces the rated interruptions of C.Bs, and CB rate is also minimized in Bismayah132kV power plant from Iraqi grid utilizing effective switching which economizes choosing CB. It is concluded that the two techniques can be used successfully for designing CB ratings with a minimum cost.